Chemically reduced organic small-molecule-based lithium battery with improved efficiency - Bhosale, Manik E.; Krishnamoorthy, Kothandam (Chemistry of Materials, 2015)
Organic lithium batteries are attractive because of the possibility of fabricating lightweight and flexible devices. However, the organic lithium batteries have a few drawbacks. The specific capacity is usually lower than the theoretical capacity, which further decreases upon cycling. Often, the specific capacity is very low compared to theoretical capacity while discharging the battery at moderate and high C rates. To circumvent this issue, we chemically reduced carboxylic acid functionality substituted perylene diimide (benzoic-PDI) with hydrazine. Indeed, we found that the rate of redox reaction as well as the conductivity of the benzoic-PDI increased upon chemical reduction. The battery comprising reduced benzoic-PDI exhibits 100% Coulombic efficiency and specific capacity while discharging at 20C. The battery also exhibits very high specific energy (213 Wh/kg) and specific power (8548 W/kg). The control experiments confirm our hypothesis of using chemical reduction to improve the performance of organic lithium battery.